Symposium 7: Roles and Identity in Scenario-Based Learning Online - King, Virginia (Proceedings of the International Conference on Networked Learning, 2006)
This paper explores the introduction of Scenario-based Learning (SBL) online and its impact on the roles and identity of the learners and academic staff involved in its adoption, as well those like myself who are in transition from ‘pedagogical developer’ to ‘pedagogical researchers’ with a focus on this pedagogy. The many issues involved are considered and their analysis presented as an ordered situational map (Clarke, 2005). A key factor that has become apparent through this reflective process is the recognition that pedagogical research is essentially individual and competitive, and that the collegiate approach so successful in pedagogical development is no longer always appropriate. A parallel is drawn with the collaborative strategies now being adopted by commercial freelance workers through such emerging online communities as Ecademy.com and OpenBC.com. These provide both a model for future pedagogical research collaboration and an example of the kind of entrepreneurial endeavor which SBL is expected to inspire in students. Universities in the UK are tasked by the UK Higher Education Funding Council to “enable people to develop their capabilities and fulfil their potential, both personally and at work” (HEFCE, 2005). The challenge to a university such as Coventry is to provide a learning experience that anticipates the needs and expectations of potential employers while satisfying the academic requirements of subject benchmarks and programmes of study. Inevitably, the emphasis on employability will create tensions for those academic staff who see this as a change in their role and/or identity. SBL also challenges learners since it requires them to adopt roles within a pre-defined situation and hence to alter their perception of the subject matter, their identity as a potential member of a community of practice and to re-frame their understanding of the boundaries of study, work and leisure.